Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Exogenous hydrogen peroxide enhanced the thermotolerance of Festuca arundinacea and Lolium perenne by increasing the antioxidative capacity - Yan Wang; Jie Zhang; Jian-Long Li; Xin-Rong Ma (Acta Physiologiae Plantarum, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Separation of the impact of climate change and human activity on streamflow in the upper and middle reaches of the Taoer River, northeastern China - Bin Li; Hongbo Su; Fang Chen; Haibin Li; Renhua Zhang; Jing Tian; Shaohui Chen; Yongming Yang; Yuan Rong (Theoretical and Applied Climatology, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Soil organic carbon stocks in the Yunnan Plateau, southwest China: spatial variations and environmental controls - Xingwu Duan; Li Rong; Jinming Hu; Guangli Zhang (Journal of Soils and Sediments, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

Three major nucleolar proteins migrate from nucleolus to nucleoplasm and cytoplasm in root tip cells of Vicia faba L. exposed to aluminum - Rong Qin; Huaning Zhang; Shaoshan Li; Wusheng Jiang; Donghua Liu (Environmental Science and Pollution Research, 2014)

Impact of Indian summer monsoon on the South Asian High and its influence on summer rainfall over China - Wei Wei; Renhe Zhang; Min Wen; Xinyao Rong; Tim Li (Climate Dynamics, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Human health risk assessment of groundwater in Hetao Plain (Inner Mongolia Autonomous Region, China) - Yilong Zhang; Rong Ma; Zhenghong Li (Environmental Monitoring and Assessment, 2014)

Cloning and expression analysis on a homolog of spermatogonial stem-cell renewal factor in Fenneropenaeus chinensis - Rong Wen; Fuhua Li; Yusu Xie; Shihao Li; Chengsong Zhang; Kuijie Yu; Jianhai Xiang (Invertebrate Reproduction & Development, 2014)

Estimate of NOX production in the lightning channel based on three-dimensional lightning locating system - Rong Zhang; GuangShu Zhang; YaJun Li; YanHui Wang; Bin Wu; Hai Yu; YanXiu Liu (Science China Earth Sciences, 2014)

Changes in the transcriptomic profiles of maize roots in response to iron-deficiency stress - Yan Li; Nian Wang; Fengtao Zhao; Xuejiao Song; Zhaohua Yin; Rong Huang; Chunqing Zhang (Plant Molecular Biology, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Attenuation of Reserpine-Induced Pain/Depression Dyad by Gentiopicroside Through Downregulation of GluN2B Receptors in the Amygdala of Mice - Shui-bing Liu; Rong Zhao; Xu-sheng Li; Hong-ju Guo; Zhen Tian; Nan Zhang; Guo-dong Gao; Ming-gao Zhao (NeuroMolecular Medicine, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

RETRACTED ARTICLE: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Characterization of masson pine (Pinus massoniana Lamb.) microsatellite DNA by 454 genome shotgun sequencing - Tian-Dao Bai; Li-An Xu; Meng Xu; Zhang-Rong Wang (Tree Genetics & Genomes, 2014)

Association between melatonin receptor 1A (MTNR1A) gene single-nucleotide polymorphisms and the velvet antler yield of Sika deer - Fei-Fei Yang; Li-Jun Huo; Li-Guo Yang; Hasan Riaz; Li-Rong Xiong; Jian-Guo Chen; Shu-Jun Zhang; Jia-Jun Xiong (Molecular Biology Reports, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Depression in older patients with advanced colorectal cancer is closely connected with immunosuppressive acidic protein - Rong Li; Jie Yang; Jihua Yang; Weijun Fu; Hua Jiang; Juan Du; Chunyang Zhang; Hao Xi; Jian Hou (Metabolic Brain Disease, 2014)

Characterization of land subsidence induced by groundwater withdrawals in the plain of Beijing city, China - Youquan Zhang; Huili Gong; Zhaoqin Gu; Rong Wang; Xiaojuan Li; Wenji Zhao (Hydrogeology Journal, 2014)

An improved embryo-rescue protocol for hybrid progeny from seedless Vitis vinifera grapes × wild Chinese Vitis species - Gui Rong Li; Wei Ji; Gang Wang; Jian Xia Zhang; Yue Jin Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)